Renewing the Paradigm of Police Science in the Era of Plural Policing - Wahyurudhanto, Albertus (Jurnal Ilmu Kepolisian, 2026)
This conceptual article examines the renewal of police science in Indonesia in response to the rise of plural policing and the gradual softening of the state’s monopoly on legitimate force. Drawing on Weber, Loader, Jones and Newburn, Johnston and Shearing, as well as recent Indonesian scholarship, the paper first maps the configuration of plural policing and the fragmentation of security actors involving Polri, the armed forces, local government units, private security providers, and community-based organisations. It then analyses the implications of this fragmentation for legitimacy, accountability, and public trust in Polri, using empirical evidence from Jakarta and related Indonesian studies. The article argues for a paradigm shift that repositions Polri as a network manager within a framework of democratic security governance and outlines key implications for regulation, oversight, professional education, and future police science research.